Legacies. The fourth and final season [videorecording (DVD)]. - Russell, Danielle Rose; Shahghasemi, Aria; Bryant, Kaylee; Davis, Matthew, 1978- (Warner Archives, 2022)
"As Season Four begins, Hope must choose between saving the boy she loves and ending Malivore's threat once and for all. This choice will have life-changing consequences for Dr. Alaric Saltzman and the Super Squad. Working together, these young and powerful vampires, witches, and werewolves - led by Lizzie and Josie Saltzman, MG, Cleo, Kaleb and their human friend Ethan - will face their darkest, deadliest challenge of all..and the Salvatore School will be torn apart in the process."--Container.